Analysis of the Impact of Mobile Banking on the Consumptive Behavior of BSI Tapaktuan Customers - Hasanah, Uswatun; Rahmadani , Ika; Mahdani , Rimal; Yanti , Fatma; Vonna, Sari Maulida (The Future of Education Journal, 2024)
This study aims to analyze the impact of mobile banking transactions on consumer behavior at PT. Bank Syariah Indonesia Tapaktuan Branch. With the advancement of fintech technology, transactions no longer need to be done physically or with cash; payments can now be made from different locations and in a quick manner. The convenience of online shopping is supported by easy payment methods, one of which is through bank transfers, such as mobile banking transfers. The method applied in this study is a quantitative approach. The sample analyzed represents a population of 96 respondents, consisting of customers of PT. Bank Syariah Indonesia (BSI) Tapaktuan Branch. The data analysis method used is simple linear regression, applying t-test analysis and the coefficient of determination (R). The study's results show a significant influence of mobile banking usage (X) on the shopping behavior (Y) of customers at PT. Bank Syariah Indonesia Tapaktuan Branch. Therefore, it can be concluded that the alternative hypothesis (Ha) indicates that mobile banking transactions influence the consumptive behavior of customers at PT. Bank Syariah Indonesia Tapaktuan Branch, and the hypothesis is accepted.